ANALISIS DAN PERENCANAAN STRUKTUR GEDUNG MENGGUNAKAN BALOK DAN PELAT BETON PRATEGANG - I Gede Gegiranang Wiryadi; I Wayan Giatmajaya; I Putu Adi Sadu Gunawan (Program Studi Teknik Sipil Fakultas Teknik Universitas Mahasaraswati Denpasar, 2021)
Beams and plates are the dominant structural elements that receive unidirectional loads, so it is possible to use a system of prestress compared to columns. In this study, the analysis and design of prestressed beams were carried out in a building that functions as a hospital and previously analyzed using ordinary reinforced concrete. Beams and plates use a composite system and a prestressive system. The beam and plate are analyzed in two stages, the production stage and the composite stage after being installed on site. At the production stage, the beam height is reduced by the plate thickness and the load is calculated only for the prestress force and the lifting process. While the composite stage or after being assembled into one with columns and plates, all forces are calculated based on all the working loads. The concrete compressive strength and the yield strength of reinforcement used are 35 MPa and 360 MPa, respectively, while the yield strength of prestressed cables is 1860 MPa. The total loss of pre-stress force is taken as 25% of the total pre-stress force. Three types of beams have a span of 8 m, namely 40 x 60 cm, 35 x 55 cm and 30 x 50 cm after the composite, while the plate thickness is 15 cm after the composite and 10 cm during production. The analysis results show that the stress that occurs in the concrete beam and slab during production and when the composite with a prestressed system does not exceed the allowable stress in accordance with regulatory provisions. So that the prestressed beams and plates with the prestressed system can be applied in a composite system to the building structure and do not exceed the allowable stress limit for receiving loads.